2004
DOI: 10.1002/marc.200300186
|View full text |Cite
|
Sign up to set email alerts
|

Double Yielding in a Styrene/Butadiene Star Block Copolymer

Abstract: Summary: The morphology and tensile deformation behaviour of a highly asymmetric styrene/butadiene star block copolymer (polystyrene (PS) content = 74%) containing random PS‐co‐PB (polybutadiene) copolymer as a rubbery phase were investigated. The existence of double yielding, similar to that observed in some semicrystalline polymers, was detected in this nanostructured amorphous polymer. The observed phenomenon may be correlated with two different micromechanical processes taking place at the initial stage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 20 publications
4
33
0
Order By: Relevance
“…This special morphology is a consequence of its special molecular architecture. 19,20 It is known that the low molar mass homopolymer can swell the corresponding block domains, leading to a transition in morphologies. 1 Assuming the structure of the star block copolymer to be intermediate between the PS cylinders and alternating lamellae, one may expect that cylinders and spheres of PS will be formed by adding different amounts of low molar mass PS004, as the latter practically increases the effective soft phase volume fraction.…”
Section: Morphology Of Block Copolymer/homopolymer Blendsmentioning
confidence: 99%
See 2 more Smart Citations
“…This special morphology is a consequence of its special molecular architecture. 19,20 It is known that the low molar mass homopolymer can swell the corresponding block domains, leading to a transition in morphologies. 1 Assuming the structure of the star block copolymer to be intermediate between the PS cylinders and alternating lamellae, one may expect that cylinders and spheres of PS will be formed by adding different amounts of low molar mass PS004, as the latter practically increases the effective soft phase volume fraction.…”
Section: Morphology Of Block Copolymer/homopolymer Blendsmentioning
confidence: 99%
“…19 The tensile stress-strain curves of the star block copolymer and its blends with PB004 and PS010 are shown in Figure 2. Owing to its morphology, comprising the cocontinuous network of PS and PS-co-PB, the star block copolymer behaves in a ductile manner (curve 3 in Fig.…”
Section: Tensile Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the existence of double yielding in nanostructured amorphous polymer was reported recently. 22 The shape of the stress-strain curve (s-e) in the double yield region may exhibit comparable values of the stress of the two maxima or a dominant value of either maximum. The stress of the first yield process becomes dominant under extreme conditions of low temperatures, high strain rates, or high crystallinities.…”
Section: Introductionmentioning
confidence: 99%
“…[5] To date, various studies have shown the existence of the double yielding phenomenon. [6][7][8][9][10][11][12][13] Segulea et al have observed the double yield behavior of several PE and related copolymers. [6] Plaza et al have studied the double yield points in triblends of low density PE, linear low density PE and EPDM, and observed that the double yield phenomenon decreased until it disappeared with increasing EPDM component.…”
Section: Introductionmentioning
confidence: 99%